A Room‐Temperature Verwey‐type Transition in Iron Oxide, Fe5O6. Issue 14 (30th January 2020) - Ovsyannikov, Sergey V.; Bykov, Maxim; Medvedev, Sergey A.; Naumov, Pavel G.; Jesche, Anton; Tsirlin, Alexander A.; Bykova, Elena; Chuvashova, Irina; Karkin, Alexander E.; Dyadkin, Vadim; Chernyshov, Dmitry; Dubrovinsky, Leonid S.
Abstract: Functional oxides whose physicochemical properties may be reversibly changed at standard conditions are potential candidates for the use in next‐generation nanoelectronic devices. To date, vanadium dioxide (VO2 ) is the only known simple transition‐metal oxide that demonstrates a near‐room‐temperature metal–insulator transition that may be used in such appliances. In this work, we synthesized and investigated the crystals of a novel mixed‐valent iron oxide with an unconventional Fe5 O6 stoichiometry. Near 275 K, Fe5 O6 undergoes a Verwey‐type charge‐ordering transition that is concurrent with a dimerization in the iron chains and a following formation of new Fe−Fe chemical bonds. This unique feature highlights Fe5 O6 as a promising candidate for the use in innovative applications. We established that the minimal Fe−Fe distance in the octahedral chains is a key parameter that determines the type and temperature of charge ordering. This model provides new insights into charge‐ordering phenomena in transition‐metal oxides in general. Abstract : Charge and order : Crystals of novel mixed‐valent iron oxide with an unconventional Fe5 O6 stoichiometry were synthesized and investigated. Near 275 K, Fe5 O6 demonstrates a Verwey‐type charge‐ordering transition that is concurrent with a pronounced dimerization and the formation of new Fe−Fe chemical bonds. This unique feature highlights Fe5 O6 as a highly promising candidate for use in innovative applications.